An improved MOEA/D algorithm for multi-objective multicast routing with network coding - Xing, Huanlai; Wang, Zhaoyuan; Li, Tianrui; Li, Hui; Qu, Rong (Elsevier, 2017)
Network coding enables higher network throughput, more balanced traffic, and securer data transmission. However, complicated mathematical operations incur when packets are combined at intermediate nodes, which, if not operated properly, lead to very high network resource consumption and unacceptable delay. Therefore, it is of vital importance to minimize various network resources and end-to-end delays while exploiting promising benefits of network coding.